English Day Program to Improve the Students’ Speaking Performance - Ega Silvia; Evi Rosmiyati; M. Ali Akbar Zam (Jurnal Pendidikan Bahasa, 2023)
This research aims to determine the application of the English day program to improve the students' speaking performance. The formulation of the problem in this research is how the English day program improve the students' speaking performance. This research used descriptive qualitative method. The data were collected by triangulation, namely observation, interview, oral tests, and documentation. In this teachers' strategy, students challenge by remember vocabulary, singing and daily conversations, then students present them in front of the class. The results of the data show that the speaking performance from students of XI Social 2 class at SMA Negeri 8 Palembang has increased but, they got special difficulties whilst the researcher gave an oral test, but the maximum common problem became their lack of confidence and vocabulary in speaking.